1991
DOI: 10.1002/ana.410300209
|View full text |Cite
|
Sign up to set email alerts
|

Uhthoff's symptom in optic neuritis: Relationship to magnetic resonance imaging and development of multiple sclerosis

Abstract: Eighty-one patients with a first attack of isolated optic neuritis, 40 with Uhthoff's symptom (Group 1) and 41 without (Group 2), were studied. All had a neurovisual examination, 74 of 81 patients had the pattern visual evoked potential recorded at rest, and 43 had magnetic resonance imaging brain scans. The pattern visual evoked potential P100 latency was prolonged, Group 1 with a mean of 136 +/- 19 msec. Group 2 with a mean of 131 +/- 19 msec (control subjects, 102 +/- 5 msec; n = 84), and the P100 amplitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Abnormalities in the cerebral white matter in these patients can be detected in 56 to 72% of cases 16 .…”
Section: Discussionmentioning
confidence: 92%
“…Abnormalities in the cerebral white matter in these patients can be detected in 56 to 72% of cases 16 .…”
Section: Discussionmentioning
confidence: 92%
“…Longer lesions of the optic nerve and involvement of the intracanalicular segment are related to slightly less complete visual recovery. 157 The presence of Uhthoff's phenomenon, transient visual blurring associated with an elevation of body temperature following optic neuritis, is most common in patients with other evidence of MS. [159][160][161][162] reported that these patients were more likely to have an abnormal MRI of the brain and that they were more likely to develop MS. Uhthoff's symptom was present in about 10% of the patients in the ONTT six months after the onset of optic neuritis. It is important to note that Uhthoff's phenomenon may also occur in healthy patients after optic neuritis, in patients with Leber's optic neuropathy, 163 and in patients with optic neuropathies from other causes.…”
Section: Diagnostic and Prognostic Testsmentioning
confidence: 96%
“…Décrit en 1870 par Wilhem Uhthoff [5], ce phénomène est associé classiquement à la SEP. McAlpine et Compston en 1952 ont constaté qu'un tiers des patients pouvaient présenter une aggravation des signes neurologiques après l'exercice physique [6]. La prévalence de ce phénomène après NO a été étudiée et varie entre 33 et 50 % selon les auteurs [7,8]. Ce phénomène peut être provoqué par toute situation entraî-nant une augmentation de la chaleur corporelle : hyperthermie, exercice physique, phase postprandiale, émotions, cycles menstruels, conditions climatiques… [7,9].…”
Section: Symptomatologieunclassified